Seismic retrofitting & energy improvement of an existing building - Ilia, Georgios (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2013)
Many existing reinforced concrete frame buildings designed before the introduction of modern seismic codes are highly vulnerable to seismic actions due to their reduced ductility capacity. Passive control systems have emerged to be efficient tools for the seismic retrofit of low ductility RC frames and help to reduce economical losses in consequence of seismic events. Since funds to investment for seismic vulnerability reduction may be limited, a riskbased life cycle cost analysis approach is required to evaluate and compare the cost effectiveness of different mitigation strategies. In this work, an existing four-storey building will be examined using two different retrofitting methods, with different remaining life and seismic return period, and conclusions will be drawn regarding the efficiency of each method in economic terms. The frame is designed for gravity-loads only and does not comply with modern seismic code requirements. Also in combination with seismic retrofitting thermal improvement of the outer shell of the building will be performed, using the regulations for thermal performance of buildings of Cyprus. Energy consumption and thermal improvement cost is a very important parameter of the whole life cost of a building. Of course it's clear that if we want to evaluate in an appropriate way the effectiveness of seismic retrofitting and thermal improvement on existing buildings, many studies should be performed to give a definitive answer to this question. In chapter one the problem is briefly stated and the most important parameters associated with that, which make the decisions for solving the problem very difficult, are presented. In chapters two and three the objectives and briefly the regulations and standardizations associated with the problem in European Union and in Cyprus are stated. In chapter four the Whole Life Cost cycle analysis (WLCCA) is briefly described, stating what is WLCCA and why it is important to be used, which data are taken into account, which are the formulas to determine the WLCCA values etc. In chapter five the methods for thermal improvement and seismic retrofitting are described, while in chapter six the methodology of seismic assessment is described. viii In chapter seven the results of the case-study and some calculations about the thermal improvement of the building, the seismic retrofitting using the software 3DR STRAD and the calculations for the WLCCA are presented. Finally, the results along with the conclusions and some discussion about the topic are represented in chapter eight. This study is a first approach on the topic and will give some results, taking into account only the most important parameters of retrofitting and thermal improvement such as commonly used materials and common working hours. More extensive work can be done if more detailed parameters are taken into account in the analysis.
Keywords: Thermal improvement; Seismic assessment and retrofitting; Life cost cycle analysis